2016
DOI: 10.1080/10942912.2016.1220393
|View full text |Cite
|
Sign up to set email alerts
|

Natural polyphenols: An overview

Abstract: Plant-derived functional foods are gaining considerable attention due to their safety and therapeutic potentials. Research on plant-based functional foods presents several challenges ranges from hypercholesterolemia to cancer prevention. In last decade, special attention has been paid to edible plants and especially their phytochemicals. Today, there is an increasing interest in their bioactivities provided by these phytochemicals. Polyphenols are the most numerous and widely distributed group of bioactive mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
315
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(376 citation statements)
references
References 95 publications
2
315
0
4
Order By: Relevance
“…This is why flavonoids always (with only a few exceptions) have an OH at C‐5 and C‐7. On the basis of the oxidation state of the central carbon, flavonoids are divided into the subgroups flavanones, flavanols, flavonols, isoflavones, flavones, and anthocyanidins ( Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…This is why flavonoids always (with only a few exceptions) have an OH at C‐5 and C‐7. On the basis of the oxidation state of the central carbon, flavonoids are divided into the subgroups flavanones, flavanols, flavonols, isoflavones, flavones, and anthocyanidins ( Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…Speculations suggested that such medical and biological uses of the Allium species might be due to the presence of organosulphur compounds (OSCs) like ajoene, diallyl disulfide (DADS) and diallyl trisulfide (DATS), S‐alk (en) yl‐ l‐cysteine sulfoxides, S‐allyl mercaptocysteine, and polysulfanes that gives them a sharp and tang smells (Kim et al, ; Putnik et al, ). Other effective compounds in these plants include carotenoids, polyphenols, anthocyanins, gallic and ferulic acids, quercetin, tricosan, alkaloids, saponins, and tannins (Abbas et al, ; Awan, Butt, Haq, Ashfaq, & Suleria, ). So far, various mechanisms including inhibition of cell cycle progression and genotoxicity, histone modification, inhibition of angiogenesis and metastasis, and induction of apoptosis have been attributed to the anticancer activities of them (Druesne et al, ; Herman‐Antosiewicz & Singh, ; Nakagawa et al, ; Singh et al, ; Türkoğlu, ).…”
Section: Introductionmentioning
confidence: 99%
“…an endogenous antioxidant enzyme. Besides, these vegetables are also considered as a rich source of dietary fiber, phytoceutics and antioxidant vitamins (Vallejo et al, 2004;Podsędek et al, 2006;Jeffery and Araya, 2009;Amnah, 2013;Al-Dosari, 2014;Park et al, 2014;Abbas et al, 2017). Furthermore, previous researchers disclosed the mineral profile of raw and cooked common cabbage that reflected higher amounts of potassium followed by calcium, magnesium and sodium, whereas trace amounts of iron, manganese, copper and zinc were also detected.…”
Section: Introductionmentioning
confidence: 99%